The impact of application acellular bovine pericardium supported with autogenous platelet-rich fibrin for cystoplasty in dogs: Histopathological assessments - Sohaib M. Amer; Fouad M. Mohammed (Iraqi Journal of Veterinary Sciences)
The experimental work was planned to determine the efficacy of an acellular bovine pericardium patch with topical application of PRF to enhance the defect of the urinary bladder in dogs. Eighteen male adult local breed dogs were utilized in this study. Animals undergo the protocol of general anesthesia. The experiment was divided randomly into two equal groups, nine for each group. In G1, acellular bovine pericardium (ABP), a circular defect about 3cm in diameter will be created on the dorsal part of the urinary bladder then the site of operation wrapped completely with 4 cm in diameter of acellular bovine pericardium, whereas in G2, acellular bovine pericardium with platelet-rich fibrin (ABP+PRF) group the site of cystoplasty was reinforced with platelet-rich fibrin. Clinically, all animals were mentioned daily for 45 days, and the histopathological and serological assessments were performed at 0, 3, 7, 15, 30, 45 days post-surgery. The results of the decellularization of the bovine pericardium (BP) patch showed the absence of cells and nuclear components. Clinically, the animals seemed healthy and survived until the completion of the study. Some signs occurred in the first 2 days, such as hematuria, pain, arching of the back and urine incontinence, which subsided after 48-72 hours post-surgery. The biochemical and serological evaluation showed an increase in the concentration of urea at day 7, 15 post-surgery and creatinine at day 7 post-surgery in G1 superior to G2. The analysis of CRP concentration showed an increase in serum CRP levels at day 3, 15 post-surgeries in G1 superior to G2. The histopathological changes were represented by good healing in both groups without inflammatory reaction at 45 days post-surgery. The healing process of UB defect was superior and earlier in G2 than in G1, represented by the formation of fibrous tissue bridges between the graft and original tissue with the neovascularization. Both groups had high vimentin expression at 45 days post-surgery, whereas there was high VEGF expression in G2 at 15, 30 days, and there was a very weak reaction in G1. In conclusion, the experimental study presented that applying PRF to the implanted ABP patch improved the healing process of bladder defects in dogs, which is important to the PRF.